A single‐crystal diamond X‐ray pixel detector with embedded graphitic electrodes. (31st March 2020) - Bloomer, C.; Newton, M. E.; Rehm, G.; Salter, P. S.
Abstract : The first experimental results from a new type of transmissive synchrotron X‐ray diagnostic instrument are presented. A chemical‐vapour‐deposition diamond plate with graphitic electrodes and a modulation lock‐in signal acquisition technique are used to image the X‐ray beam. Abstract : The first experimental results from a new transmissive diagnostic instrument for synchrotron X‐ray beamlines are presented. The instrument utilizes a single‐crystal chemical‐vapour‐deposition diamond plate as the detector material, with graphitic wires embedded within the bulk diamond acting as electrodes. The resulting instrument is an all‐carbon transmissive X‐ray imaging detector. Within the instrument's transmissive aperture there is no surface metallization that could absorb X‐rays, and no surface structures that could be damaged by exposure to synchrotron X‐ray beams. The graphitic electrodes are fabricated in situ within the bulk diamond using a laser‐writing technique. Two separate arrays of parallel graphitic wires are fabricated, running parallel to the diamond surface and perpendicular to each other, at two different depths within the diamond. One array of wires has a modulated bias voltage applied; the perpendicular array is a series of readout electrodes. X‐rays passing through the detector generate charge carriers within the bulk diamond through photoionization, and these charge carriers travel to the nearest readout electrode under the influence of the modulated electrical bias. Each of the crossing points between perpendicular wires acts as an individual pixel. The simultaneous read‐out of all pixels is achieved using a lock‐in technique. The parallel wires within each array are separated by 50 µm, determining the pixel pitch. Readout is obtained at 100 Hz, and the resolution of the X‐ray beam position measurement is 600 nm for a 180 µm size beam.